Fore-arc structure, plate coupling and isostasy in the Central Andes: Insight from gravity data modelling. (February 2017) - Rutledge, Sophia; Mahatsente, Rezene
Abstract: The central segment of the Peru-Chile subduction zone has not seen a major earthquake of similar scale to the megathrust Iquique event in 1877 (Magnitude ∼8.8). The plate interface between the subducting and overriding plates in the central segment of the subduction zone is highly coupled and is accumulating elastic energy. Here, we assessed the locking mechanism and isostatic state of the Central Andes based on gravity models of the crust and upper mantle structure. The density models are based on satellite gravity data and are constrained by velocity models and earthquake hypocenters. The gravity models indicate a high density batholithic structure in the fore-arc, overlying the subducting Nazca plate. This high density crustal structure is pressing downward into the slab and locking the plate interface. Thus, plate coupling in the Central Andes may result from pressure exerted by high density fore-arc structures and buoyancy force on the subducting Nazca plate. The increased compressive stress closer to the trench, due to the increased contact between the subducting and overriding plates, may increase the intraplate coupling in the Central Andes. To assess the isostatic state of the Central Andes, we determined the residual topography of the region (difference between observed and isostatic topography). There is a residual topography of ∼800 m in the western part of the Central Andes that cannot be explained by the observed crustal thicknesses. The residual topography may be attributed to mantle wedge flow and subduction of the Nazca plate. Thus, part of the observed topography in the western part of the Central Andes may be dynamically supported by mantle wedge flow below the overriding plate.